2010
DOI: 10.1158/0008-5472.can-10-1854
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Running Prevents Progressive Memory Decline and Increases Adult Hippocampal Neurogenesis and Growth Factor Expression after Whole-Brain Irradiation

Abstract: Whole-brain irradiation (WBI) therapy produces progressive learning and memory deficits in patients with primary or secondary brain tumors. Exercise enhances memory and adult hippocampal neurogenesis in the intact brain, so we hypothesized that exercise may be an effective treatment to alleviate consequences of WBI. Previous studies using animal models to address this issue have yielded mixed results and have not examined potential molecular mechanisms. We investigated the short-and long-term effects of WBI on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 48 publications
5
85
0
6
Order By: Relevance
“…However, it also remains possible that genes and pathways possibly involved in cell turnover, and not dopamine signaling pathways in the NAc, may be an inherent driver in running phenotypes between HVRs vs. LVRs. This finding is quite intriguing, given that adult neurogenesis, while known to be increased in the dentate gyrus in response to voluntary exercise (33,48), has been less investigated in the NAc.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also remains possible that genes and pathways possibly involved in cell turnover, and not dopamine signaling pathways in the NAc, may be an inherent driver in running phenotypes between HVRs vs. LVRs. This finding is quite intriguing, given that adult neurogenesis, while known to be increased in the dentate gyrus in response to voluntary exercise (33,48), has been less investigated in the NAc.…”
Section: Discussionmentioning
confidence: 99%
“…Ekdahl et al (1) reported that the LPS-induced inflammation remarkably reduced the number of new neurons, the BrdU-immunoreactive cells double-labeled with NeuN in the subgranular zone of the dentate gyrus. On the other hand, physical exercise improved memory function and spatial learning ability through the enhancement of neurogenesis, which was ascertained by increasing the number of BrdU-and NeuN-double positive neurons (31).…”
Section: Discussionmentioning
confidence: 99%
“…57,58 It is now known that although radiation kills rapidly dividing neural progenitor cells, the more quiescent neural stem cells (NSCs) remain viable after brain radiation, albeit in a persistently quiescent state only modestly responsive to proneurogenic stimuli such as voluntary physical exercise and mitogenic stimulation. 60,93 Unfortunately, radiation's failure to kill quiescent NSCs mirrors its inability to kill quiescent glioma stem cells, which reestablish a typically more aggressive and resistant recurrent malignancy.…”
Section: Impact Of Radiation On Neurogenesis and Neuronal Functionmentioning
confidence: 99%